2020
DOI: 10.1155/2020/1273031
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Mucosa Status and the Correlation between the Functional Parameters and the Level of Nitric Oxide Metabolites in Saliva among Patients with GERD

Abstract: The study involved 91 patients (48 women and 43 men), aged from 18 to 70 years with GERD. All patients underwent the clinical dental examination according to a single scheme including general clinical manifestations (nausea, single vomiting, belching, heartburn, pain in the epigastrium and around the navel, and poor appetite) and dental manifestations of GERD. The objective assessment of the dental status of the examined patients included the measurement of the functional parameters of the mixed saliva, buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
1
1
Order By: Relevance
“…During day one, three subjects suffered from motion sickness and had vomiting episodes. Although cortisol is known to correlate with acute nausea and vomiting 43 , 44 , we found no significant correlation between this hormone and the seasickness scale questionnaires administered 14 , 27 . Nonetheless, we have been able to measure nitric oxide metabolites (NOx) levels throughout the navigation.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…During day one, three subjects suffered from motion sickness and had vomiting episodes. Although cortisol is known to correlate with acute nausea and vomiting 43 , 44 , we found no significant correlation between this hormone and the seasickness scale questionnaires administered 14 , 27 . Nonetheless, we have been able to measure nitric oxide metabolites (NOx) levels throughout the navigation.…”
Section: Discussioncontrasting
confidence: 76%
“…Nonetheless, we have been able to measure nitric oxide metabolites (NOx) levels throughout the navigation. Nitric oxide is involved in many gastrointestinal mucosal mechanisms 26 , and previous studies found a correlation between salivary and serum NO levels with vomiting syndromes and Gastroesophageal Reflux Disease (GERD) 43 46 . Nausea caused by motion sickness is also characterized by gastric dysrhythmias 47 .…”
Section: Discussionmentioning
confidence: 99%